2010
DOI: 10.1186/cc8262
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria evaluated as a biomarker in patients with septic shock

Abstract: IntroductionWe previously showed that erythropoietin (EPO) attenuates the morphological signs of spinal cord ischemia/reperfusion (I/R) injury in swine [1] without, however, improving neurological function. The clinical use of EPO has been cautioned most recently due to serious safety concerns arising from an increased mortality in acute stroke patients treated with EPO and simultaneously receiving systemic thrombolysis [2]. Carbamylated EPO (cEPO) is an EPO derivative without erythropoietic activity and devo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…[6] In a study done by Grion et al, median ACR at 3rd day of admission was 61.8 among survivors and median ACR at 3rd of admission was 137.02 among non survivors, indicating its prognostic significance. [23] In a study done by Bhavita et al, median ACR2 at 24 hours of admission was 46 among survivors and median ACR2 at 24 hours of admission was 164.5, p value was <0.0001 which was statistically significant, indicating its prognostic significance. [24] In a study conducted by Mackinnon et al, concluded ACR measured 6hour after post admission to ICU showed a significant difference (p =0.01) among survivors & non survivors, permitting identification of patients at Increased risk of development of organ failure and death.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…[6] In a study done by Grion et al, median ACR at 3rd day of admission was 61.8 among survivors and median ACR at 3rd of admission was 137.02 among non survivors, indicating its prognostic significance. [23] In a study done by Bhavita et al, median ACR2 at 24 hours of admission was 46 among survivors and median ACR2 at 24 hours of admission was 164.5, p value was <0.0001 which was statistically significant, indicating its prognostic significance. [24] In a study conducted by Mackinnon et al, concluded ACR measured 6hour after post admission to ICU showed a significant difference (p =0.01) among survivors & non survivors, permitting identification of patients at Increased risk of development of organ failure and death.…”
Section: Methodsmentioning
confidence: 97%
“…[22] Grion et al too showed males as majority (63.3%). [23] Bhavita et al majority of the patients was males (53%). [24] In our study, Microalbuminuria occurred in 68% of the patient .Thoreveska et al showed occurrence of microalbuminuria in 69% patient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation